Analisis Pengaruh Stunting Terhadap Tingkat Produktivitas Tenaga Kerja di Indonesia Tahun 2001-2022 - Faizah, Nuralifatul; Geffinsya Ardatha Wahyu Risqilla2, Geffinsya Ardatha Wahyu (Universitas Negeri Padang, 2025)
Indonesia faces serious challenges in developing the quality of human resources, namely stunting or a condition of failure to thrive in children. Not only does it have an impact on health aspects in the short term, stunting also has a long-term impact on labor productivity and the economy. This study aims to analyze the effect of stunting prevalence, birth rate, and prevalence of food insufficiency on labor productivity in Indonesia and its implications for economic losses in the period 2001-2022. This study applies the Ordinary Least Squares method. Secondary data used comes from data in World Bank and BPS publications. The estimation results obtained that the birth rate has a significant positive effect on labor productivity in Indonesia. Meanwhile, the prevalence of stunting and the prevalence of food insufficiency have a significant negative effect on labor productivity in Indonesia. These findings emphasize the importance of nutritional interventions and food security in the development of human resource quality and the need for policies that consider the balance between population growth and improving the quality of the workforce.